The Clipped Life of the Wife in Edith Whartonâ€™S Short Story Entitled â€œA Journeyâ€ - Asmarani, Ratna (Universitas Negeri Semarang, 2021)
The purpose of this paper is to analyze the life of the young wife that is clipped by many â€œotheringâ€ factors that prevent her from becoming a Self. The analysis is focused on the â€œotheringâ€ factors and the impacts on the young wife and on her relationship with her sick husband. The analysis is done through the perspective of existentialism combining the existentialism of Sartre and Beauvoir. Since the focus is on the female character, the particular perspective used is on the existential feminism focusing on the â€œwoman-being-for-othersâ€ mode of being. The methods of research are the combination of library research method with its close-reading technique, the qualitative method, and the contextual method of literary analysis. The result shows that it is difficult for a wife to be a Self when she has to face many â€œotheringâ€ factors such as the husbandâ€™s illness, the doctorsâ€™ suggestion to move to a temperate climate State, the new environment, and the death of the husband while they are still on the train. These â€œotheringâ€ factors do not only clip the wifeâ€™s socialization, love and relationship with her husband, and anticipation to return home, but also clip the wifeâ€™s life so that she will never have a chance to be a Self forever.